A survey of ixodid ticks feeding on cattle and prevalence of tick-borne pathogens in the Black Sea region of Turkey - Aktas, Munir; Altay, Kursat; Ozubek, Sezayi; Dumanli, Nazir (Elsevier, 2012)
The study reports the frequency of infestation and the prevalence of tick-borne pathogens in feeding adult ticks detached from cattle in two climatic zones of the Black Sea region of Turkey. A total of 2160 adult ticks were collected during 2007-2008. Of these, 1062 were randomly selected, divided into 224 pools, and tested for the presence of bovine Theileria, Babesia, and Anaplasma species. Eleven tick species were recognized on cattle in the study. Hyalomma marginatum was widely disrubuted in the semi-arid bioclimatic zone, but few specimens were collected in the humid bioclimatic zone. The most prevalent tick species in the humid climatic zone was Ixodes ricinus. Infection rates were calculated as the maximum likelihood estimation with 95% confidence intervals (CI). Overall, 4% (CI 2.87-5.44) of 224 tick pools were found to be positive for the pathoges by Reverse line blot. Maximum likelihood estimation of the infection rate varied among tick species, ranging from 2.68% (CI 0.16-12.68) in Haemaphysalis sulcata to 10.49% (CI 4.07-23.66) in Rhipicephalus bursa. The most prevalent tick-borne pathogen was Anaplasma phagocytophilum at 6.78% (CI 3.41-12.18) followed by A. centrale (6.56%, CI 0.42-31.47), Anaplasma/Ehrlichia spp. (3.61%, CI 1.99-6.06), Babesia spp. (3.33%, CI 1.65-6.03), and T. buffeli/orientalis (2.71%, CI 0.73-7.18). Sequencing results indicated that Babesia spp. shared 99% to 100% similarity with the unnamed Babesia sp. Kashi 1 and 2, Babesia sp. Kayseri 1 and Babesia sp.CS58. Anaplasma/Ehrlichia spp. were 98% and 100% identical to Ehrlichia canis and Ehrlichia sp. Omatjenne strain, respectively. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Tick; Tick-borne pathogens; PCR; RLB